Is surgery indicated for elderly patients with early stage nonsmall cell lung cancer, in the era of stereotactic body radiotherapy?. Issue 43 (October 2016) - Nguyen, Nam P.; Godinez, Juan; Shen, Wei; Vinh-Hung, Vincent; Gorobets, Helena; Thariat, Juliette; Ampil, Fred; Vock, Jacqueline; Karlsson, Ulf; Chi, Alexander
Abstract: Background: The aim of this article is to assess the influence of comorbidities among elderly patients (at least 70 year old) undergoing surgery for early stage nonsmall cell lung cancer (NSCLC) and to explore the tolerability and efficacy of surgery in relation to stereotactic body radiotherapy (SBRT) in this patient population. Methods: A review of the literature on the prevalence of comorbidities among elderly patients with early stage NSCLC, and the impact of comorbidity factors on survival following surgery was conducted. Survival rates and the incidence of complications following SBRT for this patient population were also identified. Results: Comorbidities in elderly patients with early stage NSCLC may preclude surgery or lead to poor survival following surgery. However, chronological age alone should not be used as a deciding factor to deny curative treatment in elderly, but fit patients. Stereotactic body radiotherapy is well tolerated by elderly lung cancer patients and may result in survival rates similar to that following surgery. Conclusion: SBRT should be the treatment of choice for early stage NSCLC in elderly patients with multiple comorbidities that preclude surgery. The roles of surgery and SBRT for elderly, -fit patients with early stage NSCLC needs to be further defined in future prospective trials.